2023
DOI: 10.1021/acsaem.2c03841
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Coated Polymer Fiber Mesh as an Ultralightweight Gas-Diffusible Current Collector for High-Energy-Density Rechargeable Lithium–Oxygen Batteries

Abstract: Lithium−oxygen batteries (LOBs) have received great attention as nextgeneration energy storage devices owing to their superior theoretical energy densities. Although there has been considerable technological progress in the field of LOBs, the development of gas diffusion layer materials at the positive oxygen electrode is limited despite their importance in providing an oxygen supply needed to achieve practical power densities. In the present study, we demonstrate the concept of a gas-diffusible current collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…Using such a setup, the concept of a gas-diffusible current collector was recently demonstrated, which combines the functions of oxygen mass transport and electron transfer with minimal mass loading. [7] For the gas-diffusible current collector for high energy density LOB, the following three factors are crucial: (i) light weight, (ii) high electrical conductivity to function as an electron transport channel, and (iii) suitable structure for an oxygen transport channel. To verify this concept, nickel-coated polymer fiber meshes were fabricated, in which the PET fiber with diameter of 27 μm is fully covered with nickel with 0.5 μm thickness (Figure 2d-2g).…”
Section: Gas Diffusion Layer and Current Collectormentioning
confidence: 99%
See 2 more Smart Citations
“…Using such a setup, the concept of a gas-diffusible current collector was recently demonstrated, which combines the functions of oxygen mass transport and electron transfer with minimal mass loading. [7] For the gas-diffusible current collector for high energy density LOB, the following three factors are crucial: (i) light weight, (ii) high electrical conductivity to function as an electron transport channel, and (iii) suitable structure for an oxygen transport channel. To verify this concept, nickel-coated polymer fiber meshes were fabricated, in which the PET fiber with diameter of 27 μm is fully covered with nickel with 0.5 μm thickness (Figure 2d-2g).…”
Section: Gas Diffusion Layer and Current Collectormentioning
confidence: 99%
“…And then, oxygen gas further transports to inside of cell in the horizontal direction. Using such a setup, the concept of a gas‐diffusible current collector was recently demonstrated, which combines the functions of oxygen mass transport and electron transfer with minimal mass loading [7] . For the gas‐diffusible current collector for high energy density LOB, the following three factors are crucial: (i) light weight, (ii) high electrical conductivity to function as an electron transport channel, and (iii) suitable structure for an oxygen transport channel.…”
Section: Design Strategy For Fabrication Of Lobs Possessing High Cell...mentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, a recent study demonstrated the use of a gas-diffusible current collector that combines the functions of oxygen mass transport and electron transfer. 9 The application of such a novel concept for the practical design of LOBs may benefit from a detailed analysis of the cell performance at low E / C values.…”
Section: Introductionmentioning
confidence: 99%
“…However, as the mature commercial Li‐ion batteries (LIBs) are approaching their maximum limit of energy density, there is a pressing need for new cell technologies that can meet the growing demands for energy density and power density in today's storage systems [5] . In addition to lithium metal batteries (LMBs) which are undergoing commercialization, advanced lithium‐sulfur batteries (LSBs), lithium‐air batteries (LABs), and anode‐free lithium batteries (AFLBs) have been developed [6–10] . The global market for lithium batteries is expected to experience sustained growth for a considerable period of time, while safety concerns mainly regarding the flammability of the organic liquid electrolytes currently in use have been frequently raised [11] .…”
Section: Introductionmentioning
confidence: 99%